Teaching Methods in Library and Information Science - Kaula, P. N. (Journal of Information and Knowledge, 1978)
Points out the need for resourceful teaching in Library and Information Science. Indicates effectiveness of different methods of teaching and use of the various media for instruction. Briefly discusses the application of these methods in the Indian context.